Predictive role of serum and urinary cytokines in invasion and recurrence of bladder cancer - Nitu Kumari; Usha Agrawal; Ashwani Kumar Mishra; Anup Kumar; Pawan Vasudeva; Nayan Kumar Mohanty; Sunita Saxena (Tumor Biology)
Urothelial cancer patients are prone to recurrence, and there is no marker to predict which cases become refractory to the immunotherapy given to these patients. Tumour behaviour is decided by the dynamics between the pro- and anti-tumorigenic cytokines. In this study, 27 cytokines were estimated in serum and urine of 72 urothelial cancer patients and 42 healthy volunteer controls. Serum cytokines IL-1RA, IL-4 and RANTES were in significantly higher concentration in serum of patients compared to controls, while IL-2 was significantly less in concentration. Patients were found to have significantly high concentrations of 12 urinary cytokines (IL-2, IL-4, IL-8, IL-10, GM-CSF, IFN-γ, IP-10, MIP-1a, PDGF, MIP-1b, RANTES and VEGF) in comparison to healthy controls. Serum VEGF and urinary IL-1ra, IL-4, IL-10, GM-CSF, IP-10, MIP-1a and MIP-1b concentrations were found significantly higher in concentration in high-grade tumours compared to low-grade tumours. There was no difference in either the serum or urinary cytokines between non-invasive and muscle-invasive cases. Serum IL-1ra, IL-6, IL-10, TNF-α and VEGF and urinary IL-1ra, IL-4, IL-8, IL-10, GM-CSF, IP-10, MIP-1a, PDGF, MIP-1b and VEGF were found to be significantly higher in recurrent patients compared to non-recurrent patients. Of these, high concentrations of urinary IL-1RA, IL-4, IL-10, IP-10, PDGF and VEGF and serum IL-1ra, IL-6, IL-10, VEGF and TNF-α were associated with poor recurrence-free survival. Poor recurrence-free survival was also seen with increasing number of cytokines showing high concentrations. The study shows that the estimation of a combination of these cytokines in minimally or non-invasive samples may act as a prognostic indicator.